AROMATERAPI CITRUS AURANTIUM MEMPENGARUHI KECEMASAN PERSALINAN KALA 1 FASE AKTIF - Dina Octa Via; Dainty Maternity; Yuli Yantina; Dewi Yuliasari (JKM (Jurnal Kebidanan Malahayati), 2021)
Background: Anxiety is a disturbance in feelings characterized by feelings of fear or worry that are deep and ongoing. Anxiety is the most common female psychological response to childbirth. Aromatherapy is the use of scents with essential oils that promote a sense of calm and help reduce anxiety.The purpose of this study was to determine the effect of Citrus aurantium aromatherapy on the level of anxiety during the first stage of active labor at RSIA Puri Betik Hati, Bandar Lampung City.Method: This type of research is quantitative, with a Quasi Experiment Design research design using a Two Group Pre–Post Test Design. The sampling technique used is Non Probability Sampling with Accidental Sampling technique. This study used 60 research samples, divided into 2 groups, namely 30 mothers in the intervention group and 30 mothers in the control group. Measurement of anxiety levels using the Hamilton Anxiety Rating Scale (HAM-A) measuring instrument, where data collection uses observation sheets and SOPs. Analysis of the data used is the Independent Sample T-Test.Results: From the results of the research conducted by the authors, it is known that the average value of the level of labor anxiety in the intervention/experiment group (Citrus aurantia Aromatherapy) was 14.93, while in the control group the average level of labor anxiety was 28.63 the significance value is 0.000, P value (0.05) means "There is an effect of Citrus aurantium aromatherapy on the level of anxiety in the first stage of active labor.Conclusion: Observation results showed that respondents who were given Citrus aurantia aromatherapy showed a significant decrease in anxiety with mild to no anxiety levels.Suggestions It is expected that health workers will provide counseling to mothers who will give birth at a risky age, basic education level, parity primipara and grande multipara, to anticipate anxiety in mothers and provide information about preparation for childbirth and how to control changes in maternal psychology so that they can anticipate anxiety during the delivery process . Keywords: Anxiety of labor, Citrus aurantium Aromatherapy. ABSTRAK Latar Belakang: Kecemasan adalah gangguan dalam perasaan yang ditandai dengan perasaan ketakutan atau kehawatiran yang mendalam dan berkelanjutan. Kecemasan adalah respon psikologis wanita yang paling umum terhadap persalinan. Aromaterapi adalah penggunaan aroma dengan minyak essensial yang meningkatkan rasa tenang dan membantu mengurangi kecemasan.Tujuan penelitian : Untuk mengetahui pengaruh aromaterapi Citrus aurantium terhadap tingkat kecemasan persalinan fase aktif kala 1 di RSIA Puri Betik Hati Kota Bandar Lampung.Metode penelitian: Jenis penelitian ini adalah kuantitatif, dengan rancangan penelitian Quasi Eksperimen Design menggunakan rancangan Two Group Pre–Post Test Design. Teknik sampling yang digunakan adalah Non Probability Sampling dengan teknik Accidental Sampling. Penelitian ini menggunakan 60 sampel penelitian, dibagi menjadi 2 kelompok yaitu 30 ibu pada kelompok intervensi dan 30 ibu pada kelompok kontrol. Pengukuran tingkat kecemasan menggunakan metode alat ukur Hamilton Anxiety Rating Scale (HAM-A), dimana pengumpulan data menggunakan lembar observasi dan SOP. Analisa data yang digunakan adalah Uji T Sampel Independen.Hasil: Dari hasil penelitian yang dilakukan oleh penulis, diketahui bahwa nilai rata-rata tingkat kecemasan persalinan pada kelompok Intervensi/eksperimen (Aromaterapi Citrus aurantium) adalah sebesar 14.93, sementara pada hasil kelompok kontrol rata-rata rata-rata tingkat kecemasan persalinan sebesar 28.63 dan nilai signifikansinya sebesar 0.000, P value ≤ α (0,05) artinya “Ada pengaruh aromaterapi Citrus aurantium terhadap tingkat kecemasan persalinan fase aktif kala 1Kesimpulan: Hasil observasi didapatkan bahwa responden yang diberikan aromaterapi Citrus aurantium menunjukkan penurunan kecemasan yang signifikan dengan tingkat kecemasan ringan hingga tidak ada kecemasan.Saran Diharapkan tenaga kesehatan melakukan konseling kepada ibu yang akan bersalin dengan umur yang berisiko, tingkat pendidikan dasar, paritas primipara dan grande multipara, untuk mengantisipasi kecemasan pada ibu  serta memberikan informasi mengenai persiapan persalinan dan cara mengendalikan perubahan psikologi ibu sehingga dapat menganisipasi kecemasan selama proses persalinan. Kata Kunci :Kecemasan persalinan, Aromaterapi Citrus aurantium.